THE EVALUATION OF SERVICE QUALITY IN FORWARDING (Perner's Contacts, 2013)
The article deals with problem of service quality in forwarding, quantification of the level of quality and evaluation of service quality. For the quality evaluation it is necessary to apply an appropriate method. The article includes also practical application of multi-criteria evaluation of quality.
Keywords: Quality; Methods; Forwarding; Services; Evaluation